Bubble Departure Diameter Prediction Uncertainty - Marko Matkovič; Boštjan Končar (Science and Technology of Nuclear Installations)
This paper presents quality assessment of a mechanistic modelling for bubble departure diameter prediction during pool boiling condition. In contrast to flow boiling process only buoyancy force with opposing surface tension force was considered as the responsible mechanisms for bubble departure. Indeed, inertia from the fluid flow around the bubble and the growth force, which describes momentum change due to the evaporation at the bubble base and condensation at the top of the bubble, were all neglected. Besides, shear lift force and quasi-steady drag force as the dominant inertia driven forces were also neglected in the assessment. Rather than trying to model bubble dynamics as precise as possible by properly addressing all the relevant mechanisms available, the work focuses on prediction accuracy of such approach. It has been shown that inlet boundary conditions with realistic experimental accuracy may lead to a significant uncertainty in the prediction of bubble departure diameter, which is intrinsically connected to the uncertainty of most heat partitioning and CHF models.